The effect of Bikram yoga on endothelial function in young and middle-aged and older adults. Issue 1 (January 2017) - Hunter, Stacy D.; Dhindsa, Mandeep S.; Cunningham, Emily; Tarumi, Takashi; Alkatan, Mohammed; Nualnim, Nantinee; Elmenshawy, Ahmed; Tanaka, Hirofumi
Summary: The purpose of this investigation was to determine if Bikram yoga, a style of heated hatha yoga, would improve endothelial function in young and middle-aged and older, healthy adults. This trial was performed in 36 young (n = 17) and middle-aged and older adults (n = 19) who completed 3 weekly Bikram yoga classes for 8 weeks. Height, body weight and body composition were determined and endothelial function was measured noninvasively using brachial artery flow-mediated dilation (FMD) before and after the intervention. No changes in body weight, BMI or body fat percentage occurred as a result of the intervention in either group. Brachial artery FMD was significantly increased in middle-aged and older (P < 0.05) but not in young adults as a result of the intervention. The results demonstrate that a relatively short-term Bikram yoga practice might significantly improve vascular endothelial function in middle-aged and older adults. While apparently healthy individuals in this study experienced no adverse events, those with preexisting conditions should take caution and consult with a physician prior to engaging in this style of yoga.